2002
DOI: 10.1023/a:1020818417949
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Epworth sleepiness scale (ESS) is widely used to evaluate degree of somnolence among Chinese patients with sleep-disordered breathing. Yet no Mandarin-Chinese translation has ever reported its validation data. In this study we translated and validated the ESS into Mandarin Chinese (CESS). We found, in 31 bilingual patients' responses to the CESS and the English ESS obtained 1-2 weeks apart did not differ significantly (10.5 +/- 3.7 vs. 9.6 +/- 3.9, p = 0.32, Wilcoxon's signed rank test) and were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(101 citation statements)
references
References 19 publications
1
97
3
Order By: Relevance
“…Unlike the previous reports in literature [9,13], this work found that patients with head and neck cancer and urologic cancer had the highest insomnia prevalence, surprisingly breast and gynecological cancer had lowest prevalence of insomnia. Regarding treatment type, we found in this study that clinical insomnia was the most associated with chemotherapy (62%), this result agrees with the findings of the literature [9,22]. Berger and Fair reported that women undergoing chemotherapy for breast cancer who had more objectively measured daytime sleep and nighttime awakenings reported more chemotherapyrelated fatigue [23].…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the previous reports in literature [9,13], this work found that patients with head and neck cancer and urologic cancer had the highest insomnia prevalence, surprisingly breast and gynecological cancer had lowest prevalence of insomnia. Regarding treatment type, we found in this study that clinical insomnia was the most associated with chemotherapy (62%), this result agrees with the findings of the literature [9,22]. Berger and Fair reported that women undergoing chemotherapy for breast cancer who had more objectively measured daytime sleep and nighttime awakenings reported more chemotherapyrelated fatigue [23].…”
Section: Discussionsupporting
confidence: 91%
“…The proposed range for normal sleep propensity is 0–10. The Chinese version of Epworth sleepiness scale also appears to have good internal consistency and reliability among Mandarin-speaking subjects as a standardized screening test of sleepiness in daily life, with the same cut-off value [20]. The PSQI is a self-report questionnaire that assesses sleep quality over a 1-month time period.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of PD was evaluated using the UPDRS and the Hoehn and Yahr stage (H&Y stage), and both scores were determined without stopping medication. Nighttime and daytime sleep problems were evaluated using the Pittsburgh Sleep Quality Index (PSQI) (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and the Epworth Sleepiness Scale (ESS), respectively (Chen et al., 2002; Johns, 1991). We evaluated the sleep problems that might be relevant to PD symptoms by using the Parkinson's Disease Sleep Scale (PDSS) (Chaudhuri et al., 2002), and the quality of life of PD patients was assessed using the 39‐Item Parkinson's Disease Questionnaire (PDQ‐39) (Jenkinson, Fitzpatrick, Peto, Greenhall, & Hyman, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Following the generally accepted criteria, we use PSQI > 5 to identify PD patients as poor sleepers (Buysse et al., 1989) and ESS ≥ 10 to identify those with daytime sleep disorders (EDS) (Chen et al., 2002; Johns, 1991). …”
Section: Methodsmentioning
confidence: 99%